2021
DOI: 10.3390/ma14175023
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Processing Influence on Microstructure, Mechanical, and Corrosion Behavior of Steels: A Review

Abstract: Friction stir processing (FSP) technology has received reasonable attention in the past two decades to process a wide range of materials such as aluminum, magnesium, titanium, steel, and superalloys. Due to its thermomechanical processing nature, FSP is used to alter grain structure and enhance mechanical and corrosion behavior in a wide range of steels. The refinement in grains and phase transformations achieved in steel after FSP affects hardness, tensile properties, fracture toughness, fatigue crack propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The significant grain refinement revealed by the results of microstructural investigations discussed earlier is the main reason for such substantial enhancement in mechanical properties upon FSP. Basically, strengthening of different steels via grain refinement was the topic of many research works [2,33,[53][54][55] as this mechanism was found to be very effective for metallic materials in general. For in-depth analysis and assessment of the obtained results, the relationships between mechanical properties and underlying elementary mechanisms are discussed in the remainder of the present work.…”
Section: Mechanical Responsementioning
confidence: 99%
“…The significant grain refinement revealed by the results of microstructural investigations discussed earlier is the main reason for such substantial enhancement in mechanical properties upon FSP. Basically, strengthening of different steels via grain refinement was the topic of many research works [2,33,[53][54][55] as this mechanism was found to be very effective for metallic materials in general. For in-depth analysis and assessment of the obtained results, the relationships between mechanical properties and underlying elementary mechanisms are discussed in the remainder of the present work.…”
Section: Mechanical Responsementioning
confidence: 99%
“…In this way, they concluded that the AZ31-fly ash composite possesses higher wear resistance as compared to AZ31 alloy [150]. It is evident that FSW and FSP techniques could have beneficial impacts on the mechanical behavior of Mg and other metallic alloys [133,[151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167]. Hence, the mechanical properties of some types of magnesium-based alloys before and after FSP are listed in Table 7.…”
Section: Mechanical Performancementioning
confidence: 99%
“…Another way to enhance the mechanical and corrosion behavior of a wide range of steels is application of the cold spray technique with friction stir processing technology. The combination of these methods helps to improve the microstructure of the material by decreasing its porosity and number of voids [68][69][70].…”
Section: Introductionmentioning
confidence: 99%